The Effectiveness Of Youtube Video To Improve English Speaking Skills Of Eighth Grade Students At SMP Negeri 19 Palu - Rai Ayu Wilena Dewi; Hastini Hastini; Grace Novenasari Manurung (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
This research investigated the effectiveness of YouTube videos in improving the English-speaking skills of eighth-grade students at SMP Negeri 19 Palu. Two groups participated in the reseach's quasi-experimental design: an experimental group that was treated using YouTube videos and a control group that was taught using conventional methods. Fluency and comprehensibility were the main goals of the speaking skills evaluation. A speaking rubric was used to collect the data through pre-tests and post-tests. Because of the non-normal distribution of the data, the Wilcoxon Signed Rank Test and the Mann-Whitney U Test were used for analysis. The results demonstrated that the experimental group's speaking scores significantly exceeded those of the control group. While the control group's mean score only improved from 29.44 to 45.00, the experimental group's reached from 36.32 to 72.11. A substantial difference (p = 0.001) between the two groups was verified by the statistical analysis, suggesting that YouTube videos are a useful tool for improving students' English-speaking skills. According to the research, including digital resources like YouTube into English language instruction can foster a more stimulating and encouraging learning environment.